Progressive Muscle Relaxation Therapy Against Anxiety in High School Students Related to the Covid-19 Pandemic - Nuraini Fitri; Hernida Warni; Niken Yuniar Sari (Jurnal Keperawatan, 2022)
In early 2020 until August 2021, the world experienced a pandemic related to the corona virus that required people to Stay At Home. Continuing with the IPK findings regarding anxiety complaints in 2020 related to the COVID-19 pandemic situation, it reached 18.9%. This research was conducted with the aim of reducing the intensity of anxiety in JHS students through progressive muscle relaxation techniques using the STAI (State-Trait Anxiety Inventory) measuring instrument. The sample in this study amounted to 18 people divided into 2 groups, namely experimental and control. This study uses a Quasy Experimental Pre-Past Test With Control Group with Purposive Sampling design.. The data collection technique used purposive sampling, univariate analysis with categorical distribution and bivariate analysis using paired sample test with 95% confidence level (α=0.05). The results showed that there was a significant difference in the level of anxiety in the experimental group before and after the intervention of progressive muscle relaxation techniques was given to anxiety in the State section, ρ value 0.000 <0.05 and the Trait section, ρ value 0.001 < 0.05, meaning that there was an effect of progressive muscle relaxation on anxiety in the experimental group at JHS UI Fitrah Insani Bandar Lampung.